The incidence of factor VIII inhibitors in severe haemophilia A following a major switch from full‐length to B‐domain‐deleted factor VIII: a prospective cohort comparison. (7th November 2014) - Hay, C. R. M.; Palmer, B. P.; Chalmers, E. A.; Hart, D. P.; Liesner, R.; Rangarajan, S.; Talks, K.; Williams, M.; Collins, P. W.; ,
Summary: Although it has been suggested that switching of factor VIII (FVIII) products may increase inhibitor formation this is disputed. Half of UK patients changed rFVIII brands because of national contracting in 2010, presenting an opportunity to compare inhibitor incidence of switchers with non‐switchers. Centres were requested to test all the patients for inhibitors prior to the switching date and 6‐monthly thereafter. Positive and negative inhibitor test data were also collected to analyse for testing bias. A total of 1198 patients with severe haemophilia A and treated with Advate, Kogenate/Helixate or Refacto AF preswitch were included in the analysis, of whom 516 switched to Refacto‐AF and 682 did not switch products. Five new inhibitors were reported amongst previously treated patients (>50 exposure days) with a median titre at the time of detection of 1.25 BU mL −1 (IQR 0.7–23.05). One inhibitor occurred in a non‐switcher using Kogenate, an incidence of 1.5 per 1000 treatment‐years (95% CI 0.2–10.5). Four inhibitors arose in patients who had switched from Kogenate (two) or Advate (two) to ReFacto‐AF, an incidence of 7.8 per 1000 treatment‐years (95% CI 2.9–20.8). These incidence rates did not differ significantly from one another (incidence rate ratio 5.3 (95% CI 0.5–260.3) or from the historical rate of 6.05 inhibitors/1000 treatment‐years (95% CI 5.18–7.06). Only one inhibitor (non‐switcher) persisted. Non‐switchers were significantly older ( P  = 0.03), and used significantly less FVIII per year ( P  = 0.005) prior to switching. Following switching, factor usage increased similarly ( P  = 0.53) in both groups. Switching from FLRFVIII to Refacto‐AF (BDDRFVIII) was not associated with an increased inhibitor development.